Method for improving performance of ceramic material based on vacuum negative pressure permeation metal solution

By using vacuum negative pressure and pressurization methods in ceramic tools, the metal solution completely penetrates into the ceramics, which solves the problem that metal solution is difficult to penetrate completely in the prior art, and significantly improves the strength and service life of the ceramic tools.

CN119504238APending Publication Date: 2025-02-25袁德禄
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411755913.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to allow metal solutions to penetrate completely into the ceramic tool, resulting in limited improvement in the performance of ceramic tool.

Method used

Using a method based on vacuum negative pressure and pressurization, the metal solution penetrates into the voids of the ceramic tool, and the air inside the ceramic is extracted through vacuum to form a negative pressure environment, and then the metal solution is injected and pressurized to make it completely penetrate.

Benefits of technology

Complete penetration of metal solutions is achieved, the toughness of ceramic tools is improved by 1-3 times, the strength is increased by 35%-50%, and the service life is extended by 35%-50%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504238A_ABST
    Figure CN119504238A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the performance of a ceramic material based on a vacuum negative-pressure infiltrating metal solution, and belongs to the technical field of performance improvement of ceramic tools. A method for improving the performance of a ceramic material based on a vacuum negative-pressure infiltrating metal solution comprises the following steps: mixing magnesium oxide, lithium carbonate, aluminum oxide, sodium carbonate, boric acid, silicon dioxide, zinc oxide and aluminum oxide powder, pressing the mixture into a ceramic tool, and firing the pressed ceramic tool to keep the porosity of the ceramic tool at 20-40%, the ceramic tool is pretreated, and impurities on the surface of the ceramic tool are removed; according to the method, the alloy solution is prepared from copper, tin, aluminum and magnesium, and the alloy solution completely permeates the ceramic tool in a negative pressure and positive pressure mode, so that the toughness of the ceramic tool can be improved by 1-3 times, the strength is improved by 35%-50%, and the service life is prolonged by 35%-50%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic tool performance improvement, and in particular to a method for improving ceramic material performance based on vacuum negative pressure infiltration of metal solution. Background Art

[0002] Tools made of ceramic materials have excellent properties such as high hardness, high wear resistance, and high temperature resistance, but they also have disadvantages such as poor toughness and poor thermal shock resistance. In order to overcome these defects, people have tried many methods to improve the performance of ceramic materials.

[0003] Traditional metal infiltration only uses negative pressure to allow the metal solution to penetrate into the ceramic after vacuuming the ceramic tool. However, this method can only allow the metal solution to penetrate into the surface of the ceramic tool, but not completely into the ceramic tool, resulting in limited improvement in the performance of the ceramic tool. Therefore, a relatively low-cost method is needed to allow the metal solution to completely penetrate into the ceramic tool to improve the performance of ceramic materials. Summary of the invention

[0004] The purpose of the present invention is to solve the problems in the prior art and to propose a method for improving the performance of ceramic materials based on vacuum negative pressure infiltration of metal solutions.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A method for improving the performance of ceramic materials based on vacuum negative pressure infiltration of metal solution, comprising the following steps: S1. Ceramic work production: magnesium oxide, lithium carbonate, aluminum oxide, sodium carbonate, boric acid, silicon dioxide, zinc oxide, and aluminum oxide powder are mixed and pressed into ceramic tools, and then the pressed ceramic tools are fired to keep the porosity of the ceramic tools at 20%-40%, and the ceramic tools are pre-treated to remove impurities on the surface; S2. Preparation of metal solution: Mix copper, tin, aluminum and magnesium in proportion and smelt them into a metal solution for standby use; S3. Vacuuming: The ceramic tool is placed in a vacuum furnace. Under the action of vacuum negative pressure, air is extracted from the pores inside the ceramic body to form a negative pressure environment, and the cavity is preheated; S4. Pressurized infiltration: After the vacuum is completed, the prepared metal solution is injected into the vacuum furnace so that the ceramic tool is completely immersed in the metal solution, and air is injected into the chamber to pressurize the metal solution so that the metal solution penetrates into the gaps of the ceramic tool; S5. Post-processing: After the infiltration is completed, the ceramic preform is taken out from the metal solution, cleaned to remove the excess metal solution on the surface, and dried. Finally, the dried ceramic tool is sintered to make the metal evenly distributed inside the ceramic.

[0006] In some embodiments, the mixing ratio of S1 is 0.7%-0.9% magnesium oxide, 0.5%-0.7% lithium carbonate, 8.5%-9.5% aluminum oxide, 10%-12% sodium carbonate, 27%-29% boric acid, 19%-21% silicon dioxide, 1.5%-2% zinc oxide, and the balance is aluminum oxide. The firing temperature is 600 degrees to 650 degrees, and the firing time is 3-8 hours.

[0007] In some embodiments, the pretreatment method in S1 is to clean the ceramic tool by soaking in an organic solvent for 1-2 hours, then rinsing with deionized water for 3-5 times, and then drying in a drying oven at 80-100° C. for 2-3 hours.

[0008] In some embodiments, the mixing ratio of the molten metal in S2 is 55%-62% copper, 27%-33% tin, 3%-6% aluminum, and the balance is magnesium, and the smelting temperature is 650-900 degrees.

[0009] In some embodiments, the vacuum in S3 reaches -0.08--0.1 MPa, and the vacuum time is 25-45 minutes.

[0010] In some embodiments, the pressurization in the chamber in S4 needs to reach 0.13-0.17 MPa and last for 1.5-4 hours.

[0011] In some embodiments, when air is injected for pressurization in S4, the molten metal and the ceramic tool can be heated simultaneously to keep the molten metal in a molten state, and the heating temperature is 650-800 degrees.

[0012] In some embodiments, the temperature of the drying process in S5 is controlled at 150-200 degrees, and the drying time is 1.5-2.5 hours.

[0013] In some embodiments, the sintering treatment temperature in S5 is 450-550 degrees, and the sintering time is 2-3 hours.

[0014] Compared with the prior art, the present invention provides a method for improving the performance of ceramic materials based on vacuum negative pressure infiltration of metal solutions, which has the following beneficial effects.

[0015] 1. The present invention adopts copper, tin, aluminum and magnesium to make alloy solution, and combines negative pressure and positive pressure to make the alloy solution completely penetrate into the ceramic tool, so as to improve the toughness of the ceramic tool by 1-3 times, the strength by 35%-50%, and the service life by 35%-50%.

[0016] 2. The present invention can effectively remove excess metal on the surface of the ceramic tool by cleaning the ceramic tool, and can ensure that the metal is evenly distributed inside the ceramic tool through precise drying and sintering treatment, thereby improving the stability of the ceramic tool.

[0017] Other advantages, objectives and features of the present invention will be described in part in the following description; and in part, will be apparent to those skilled in the art based on an examination of the following; or, may be taught from the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a schematic diagram of the process flow of the present invention.

[0019] Figure 2 The figure is a schematic diagram of the process flow of making ceramic tools in the present invention.

[0020] Figure 3 It is a schematic diagram of the process flow of pressurized infiltration in the present invention.

[0021] Figure 4 It is a schematic diagram of the process flow of post-processing in the present invention. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0023] Reference Figure 1-4 A method for improving the performance of ceramic materials based on vacuum negative pressure infiltration of metal solutions, comprising the following steps: mixing magnesium oxide, lithium carbonate, aluminum oxide, sodium carbonate, boric acid, silicon dioxide, zinc oxide, and aluminum oxide powders and pressing them into ceramic tools, the mixing ratio being 0.7%-0.9% magnesium oxide, 0.5%-0.7% lithium carbonate, 8.5%-9.5% aluminum oxide, 10%-12% sodium carbonate, 27%-29% boric acid, 19%-21% silicon dioxide, 1.5%-2% zinc oxide, and the balance being aluminum oxide, and then firing the pressed ceramic tools at a firing temperature of 600-650 degrees, a heating rate of 50-100 ℃ / hour, and a firing time of 3-8 hours, so that the porosity inside the ceramic tools reaches 20%-40%, and then naturally cooling to room temperature to avoid cracking due to rapid cooling.

[0024] It can be understood that magnesium oxide can improve the mechanical strength and heat resistance of ceramics, lithium carbonate is used to improve the solubility of ceramics and reduce the firing temperature, aluminum oxide can improve the wear resistance, refractoriness and mechanical strength of ceramics, sodium carbonate can be used as a flux to help reduce the melting temperature, boric acid as a flux can help form a vitrified phase and improve the strength of ceramics, silicon dioxide provides skeleton support, zinc oxide toughens and improves color, and meets the use requirements of strength, thermal stability and porosity.

[0025] Specifically, after the ceramic tool is manufactured, it is soaked in ethanol for 1-2 hours, then rinsed with deionized water for 3-5 times, and then dried in a drying oven at 80-100° C. for 2-3 hours to clean the ceramic tool and remove impurities on the surface.

[0026] It can be understood that the deep cleaning and drying treatment in the above manner can effectively remove impurities on the surface and in the gaps of the ceramic tool.

[0027] Specifically, copper, tin, aluminum and magnesium are mixed in proportion and smelted into molten metal, the mixing ratio is 55%-62% copper, 27%-33% tin, 3%-6% aluminum, and the balance is magnesium, and the smelting temperature is 650-900 degrees.

[0028] It is understandable that copper has extremely high electrical and thermal conductivity, which can significantly enhance the electrical and thermal properties of ceramic tools, making them more advantageous in electrical engineering and high-temperature applications, while improving the toughness and corrosion resistance of ceramics. Tin has good wettability and adhesion, which can effectively enhance the bonding strength of the metal-ceramic interface and improve the stability of the overall structure. The addition of aluminum can significantly improve the hardness and wear resistance of ceramic tools, making the tools more durable during high-speed cutting and grinding. Magnesium alloying can improve the mechanical strength of ceramics, especially under high temperature conditions. The lightweight characteristics of magnesium can also reduce the total weight of the tool. Magnesium has good antioxidant properties. Adding it to ceramic tools can improve its durability in an oxidizing environment. The ductility of copper and aluminum can improve the toughness of ceramic materials, making them less prone to breakage when subjected to impact.

[0029] Specifically, the processed ceramic tools are placed in a vacuum furnace and evacuated to -0.08--0.1MPa for 25-45 minutes. Under the action of vacuum negative pressure, the air is extracted from the pores inside the ceramic body to form a negative pressure environment, and the cavity is preheated at a temperature of 550-700 degrees.

[0030] It is understandable that the vacuum environment will gradually draw out the air in the pores inside the ceramic body. Due to the pressure difference, gas molecules are continuously removed, forming a negative pressure environment, which facilitates the subsequent alloy solution to penetrate into the interior of the ceramic tool.

[0031] Specifically, after the vacuuming is completed, the prepared metal solution is injected into the vacuum furnace so that the ceramic tool is completely immersed in the metal solution, and air is injected into the chamber to pressurize it to 0.13-0.17 MPa for 1.5-4 hours. At the same time, the metal solution and the ceramic tool are heated, and the temperature is maintained at 650-800 degrees to keep the metal solution in a molten state and allow the metal solution to penetrate into the gaps in the ceramic tool.

[0032] It can be understood that by pressurizing the chamber, the metal solution can completely penetrate the pores within the ceramic tool, avoiding the metal solution from penetrating only the surface of the ceramic tool. By completely penetrating the metal solution into the interior of the ceramic tool, the overall structure of the tool is strengthened, thereby improving its toughness and service life.

[0033] Specifically, after the infiltration is completed, the ceramic tool is taken out of the metal solution and cleaned with an ultrasonic cleaner to remove excess metal solution on the surface, and then placed in a drying furnace for drying. The drying temperature is controlled at 150-200 degrees and the drying time is 1.5-2.5 hours. Finally, the dried ceramic tool is sintered at a sintering temperature of 450-550 degrees and a sintering time of 2-3 hours to make the metal evenly distributed inside the ceramic.

[0034] It is understandable that by cleaning the ceramic tool, the excess metal on the surface of the ceramic tool can be effectively removed, and through precise drying and sintering processes, the metal can be ensured to be evenly distributed inside the ceramic tool, thereby significantly improving the performance of the ceramic tool.

[0035] Example 1 S1. Take 0.8% magnesium oxide, 0.6% lithium carbonate, 9% aluminum oxide, 11% sodium carbonate, 28% boric acid, 20% silicon dioxide, 1.7% zinc oxide, and 28.9% aluminum oxide in proportion, mix and press, then fire the pressed ceramic tool at a temperature of 650 degrees, a heating rate of 80 degrees Celsius / hour, and a firing time of 6 hours, so that the porosity inside the ceramic tool reaches 30%, and then cool naturally to room temperature to avoid cracking due to rapid cooling.

[0036] S2. After the ceramic tool is made, soak it in ethanol for 2 hours, rinse it with deionized water 5 times, and then dry it in a drying oven at 90°C for 2 hours to clean the ceramic tool and remove impurities on the surface.

[0037] S3. Take 58% copper, 30% tin, 4.5% aluminum and 7.5% magnesium and melt them into molten metal at a melting temperature of 800 degrees.

[0038] S4. Place the processed ceramic tools into a vacuum furnace and evacuate to -0.1MPa for 25 minutes. Under the action of vacuum negative pressure, the air is extracted from the pores inside the ceramic body to form a negative pressure environment, and the cavity is preheated at 700 degrees.

[0039] S5. After the vacuuming is completed, the prepared metal solution is injected into the vacuum furnace so that the ceramic tool is completely immersed in the metal solution, and air is injected into the chamber to pressurize it to 0.15 MPa for 3 hours. At the same time, the metal solution and the ceramic tool are heated at 800 degrees to keep the metal solution in a molten state and allow the metal solution to penetrate into the gaps in the ceramic tool.

[0040] S6. After the infiltration is completed, the ceramic tool is taken out from the metal solution and cleaned with an ultrasonic cleaner to remove excess metal solution on the surface. Then, the tool is placed in a drying furnace for drying. The drying temperature is controlled at 180 degrees and the drying time is 2 hours. Finally, the dried ceramic tool is sintered at a temperature of 500 degrees and a sintering time of 2.5 hours to make the metal evenly distributed inside the ceramic.

[0041] Example 2 S1. Take 0.7% magnesium oxide, 0.5% lithium carbonate, 8.5% aluminum oxide, 10% sodium carbonate, 27% boric acid, 21% silicon dioxide, 2% zinc oxide, and 30.3% aluminum oxide in proportion, mix and press, then fire the pressed ceramic tool at a temperature of 600 degrees, a heating rate of 50 degrees Celsius / hour, and a firing time of 8 hours, so that the porosity inside the ceramic tool reaches 20%, and then naturally cool to room temperature to avoid cracking due to rapid cooling.

[0042] S2. After the ceramic tool is made, soak it in ethanol for 1 hour, rinse it with deionized water 3 times, and then dry it in a drying oven at 80°C for 3 hours to clean the ceramic tool and remove impurities on the surface.

[0043] S3. Take 55% copper, 33% tin, 6% aluminum and 6% magnesium and melt them into molten metal at a melting temperature of 900 degrees.

[0044] S4. Place the processed ceramic tools into a vacuum furnace and evacuate to -0.08MPa for 45 minutes. Under the action of vacuum negative pressure, the air is extracted from the pores inside the ceramic body to form a negative pressure environment, and the cavity is preheated at 550 degrees.

[0045] S5. After the vacuuming is completed, the prepared metal solution is injected into the vacuum furnace so that the ceramic tool is completely immersed in the metal solution, and air is injected into the chamber to pressurize it to 0.13 MPa for 4 hours. At the same time, the metal solution and the ceramic tool are heated and the temperature is maintained at 650 degrees to keep the metal solution in a molten state and allow the metal solution to penetrate into the gaps in the ceramic tool.

[0046] S6. After the infiltration is completed, the ceramic tool is taken out from the metal solution and cleaned with an ultrasonic cleaner to remove excess metal solution on the surface. Then, it is placed in a drying furnace for drying. The drying temperature is controlled at 200 degrees and the drying time is 1.5 hours. Finally, the dried ceramic tool is sintered at a sintering temperature of 450 degrees and a sintering time of 3 hours to make the metal evenly distributed inside the ceramic.

[0047] Example 3 S1. Take 0.9% magnesium oxide, 0.7% lithium carbonate, 9.5% aluminum oxide, 12% sodium carbonate, 29% boric acid, 21% silicon dioxide, 2% zinc oxide, and 24.9% aluminum oxide in proportion, mix and press, then fire the pressed ceramic tool at a temperature of 630 degrees, a heating rate of 100 degrees Celsius / hour, and a firing time of 4 hours, so that the porosity inside the ceramic tool reaches 40%, and then naturally cool to room temperature to avoid cracking due to rapid cooling.

[0048] S2. After the ceramic tool is made, soak it in ethanol for 2 hours, rinse it with deionized water 5 times, and then dry it in a drying oven at 100°C for 2 hours to clean the ceramic tool and remove impurities on the surface.

[0049] S3. Take 62% copper, 27% tin, 3% aluminum and 8% magnesium and melt them into molten metal at a melting temperature of 700 degrees.

[0050] S4. Place the processed ceramic tools into a vacuum furnace and evacuate to -0.08MPa for 45 minutes. Under the action of vacuum negative pressure, the air is extracted from the pores inside the ceramic body to form a negative pressure environment, and the cavity is preheated at 650 degrees.

[0051] S5. After the vacuuming is completed, the prepared metal solution is injected into the vacuum furnace so that the ceramic tool is completely immersed in the metal solution, and air is injected into the chamber to pressurize it to 0.17 MPa for 1.5 hours. At the same time, the metal solution and the ceramic tool are heated and the temperature is maintained at 750 degrees to keep the metal solution in a molten state and allow the metal solution to penetrate into the gaps in the ceramic tool.

[0052] S6. After the infiltration is completed, the ceramic tool is taken out from the metal solution and cleaned with an ultrasonic cleaner to remove excess metal solution on the surface. Then, the tool is placed in a drying furnace for drying. The drying temperature is controlled at 150 degrees and the drying time is 1.5 hours. Finally, the dried ceramic tool is sintered at a temperature of 550 degrees and a sintering time of 2 hours to make the metal evenly distributed inside the ceramic.

[0053] Comparative Example Take 0.7% magnesium oxide, 0.5% lithium carbonate, 8.5% aluminum oxide, 10% sodium carbonate, 27% boric acid, 21% silicon dioxide, 2% zinc oxide, and 30.3% aluminum oxide in proportion, mix and press, then fire the pressed ceramic tool at a temperature of 600 degrees, the heating rate is controlled at 50 ℃ / hour, and the firing time is 8 hours, so that the porosity inside the ceramic tool reaches 20%, and then cool naturally to room temperature to avoid cracking due to rapid cooling.

[0054] Table 1 Ceramic tool performance test results The test results show that: compared with Example 3, Example 1 and Example 2 increase the tin content, reduce the proportion of other metals, enhance the bonding strength between metal and ceramic, increase the smelting temperature, make the metal solution flow and penetrate better, and improve the overall strength, toughness and service life. Compared with the comparative example, Example 1, Example 2 and Example 3 increase the toughness of the ceramic tool by 1-3 times, increase the strength by 35%-50%, and increase the service life by 35%-50%.

[0055] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0056] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0057] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for improving the performance of ceramic materials based on vacuum negative pressure infiltration of metal solution, characterized in that: The following steps are involved: S1. Ceramic work production: magnesium oxide, lithium carbonate, aluminum oxide, sodium carbonate, boric acid, silicon dioxide, zinc oxide, and aluminum oxide powder are mixed and pressed into ceramic tools, and then the pressed ceramic tools are fired to keep the porosity of the ceramic tools at 20%-40%, and the ceramic tools are pre-treated to remove impurities on the surface; S2. Preparation of metal solution: Mix copper, tin, aluminum and magnesium in proportion and smelt them into a metal solution for standby use; S3. Vacuuming: The ceramic tool is placed in a vacuum furnace. Under the action of vacuum negative pressure, air is extracted from the pores inside the ceramic body to form a negative pressure environment, and the cavity is preheated; S4. Pressurized infiltration: After the vacuum is completed, the prepared metal solution is injected into the vacuum furnace so that the ceramic tool is completely immersed in the metal solution, and air is injected into the chamber to pressurize the metal solution so that the metal solution penetrates into the gaps of the ceramic tool; S5. Post-processing: After the infiltration is completed, the ceramic preform is taken out from the metal solution, cleaned to remove the excess metal solution on the surface, and dried. Finally, the dried ceramic tool is sintered to make the metal evenly distributed inside the ceramic.

2. A method for improving the performance of ceramic materials based on vacuum negative pressure infiltration of metal solution according to claim 1, characterized in that: The mixing ratio of S1 is 0.7%-0.9% magnesium oxide, 0.5%-0.7% lithium carbonate, 8.5%-9.5% aluminum oxide, 10%-12% sodium carbonate, 27%-29% boric acid, 19%-21% silicon dioxide, 1.5%-2% zinc oxide, and the balance is aluminum oxide. The firing temperature is 600 degrees to 650 degrees, and the firing time is 3-8 hours.

3. The method for improving the performance of ceramic materials based on vacuum negative pressure infiltration of metal solution according to claim 1, characterized in that: The pretreatment method in S1 is to soak the ceramic tool in an organic solvent for 1-2 hours, then rinse it with deionized water for 3-5 times, and then dry it in a drying oven at 80-100° C. for 2-3 hours to clean the ceramic tool.

4. The method for improving the performance of ceramic materials based on vacuum negative pressure infiltration of metal solution according to claim 1, characterized in that: The mixing ratio of the molten metal in the S2 is 55%-62% copper, 27%-33% tin, 3%-6% aluminum, and the balance is magnesium, and the smelting temperature is 650-900 degrees.

5. The method for improving the performance of ceramic materials based on vacuum negative pressure infiltration of metal solution according to claim 1, characterized in that: The vacuum in S3 reaches -0.08--0.1MPa, and the vacuum time is 25-45 minutes.

6. The method for improving the performance of ceramic materials based on vacuum negative pressure infiltration of metal solution according to claim 1, characterized in that: In the S4, the pressure in the chamber needs to reach 0.13-0.17 MPa and last for 1.5-4 hours.

7. The method for improving the performance of ceramic materials based on vacuum negative pressure infiltration of metal solution according to claim 1, characterized in that: When air is injected into the S4 for pressurization, the molten metal and the ceramic tool are heated at the same time to keep the molten metal in a molten state, and the heating temperature is 650-800 degrees.

8. The method for improving the performance of ceramic materials based on vacuum negative pressure infiltration of metal solution according to claim 1, characterized in that: The temperature of the drying process in S5 is controlled at 150-200 degrees, and the drying time is 1.5-2.5 hours.

9. The method for improving the performance of ceramic materials based on vacuum negative pressure infiltration of metal solution according to claim 1, characterized in that: The sintering temperature in S5 is 450-550 degrees, and the sintering time is 2-3 hours.

Citation Information

Cited By

  • Preparation method of zinc oxide-aluminum oxide ceramic bone repair scaffold

    CN120682021A